KEDUDUKAN YAYASAN : ANTARA PENDIRI DAN MASYARAKAT - Lintang Suryaningtyas (Universitas Katolik Indonesia Atma Jaya, 2019)
The foundation as a form of legal entity in Indonesia has a unique character because it is owned by the public, has no members, and is engaged in social, religious and humanitarian fields. The founder separates a portion of his personal assets and surrenders fully to the foundation he founded. After that, the founder may sit as the organ of the foundation that he founded, although that is not compulsory, as well as the family members of the founder of the foundation which are a completely separate part and may not have any interest in the foundation. The foundation’s establishment is relatively easy, but its management requires carefulness in order not to cause legal problems among the organs, the organs the founder and other legal problems that may effect the foundations themselves. The founding of the foundation since the era of Hindia Belanda without being regulated by laws and regulations in Indonesia, raises its own resistance for descendants of the founders of foundations and foundation managers who are accustomed to manage foundations with free play rules, when the birth of the Republic of Indonesia Law Number 16 of 2001 Concerning Foundations then amended by Law of the Republic of Indonesia Number 28 of 2004 concerning Amendments to the Law of the Republic of Indonesia Number 16 of 2001 concerning Foundations, along with the implementing regulations. Efforts to enforce the provisions in the Law of the Foundation seem to indeed require some significant amount of time, so that within a period of almost two decades since the enactment of the Foundation Law, there are still many ignorance of the provisions regarding foundations and conflicts that resulted from such ignorance.